FUNDRAISING IN THE CREATIVE AND CULTURAL INDUSTRIES leading effective fundraising... strategies. - Wright, Michelle ([S.l.] : ROUTLEDGE, 2022)
The need for effective fundraising in the arts has never been more acute. Specialist yet accessible, Fundraising in the Creative and Cultural Industries is designed to provide strategic and practical support to individuals needing to lead or develop fundraising in their organisations. Part One explores theories of leadership and change, as well as managing fundraising in a crisis, most notably the impact of COVID-19 on cultural organisations globally. It introduces readers to specific academic frameworks and concepts from arts management, business and entrepreneurship studies - which readers can use to analyse their own situations - and provides insight via real-world case studies. Part Two explores the practical application of fundraising. Readers can begin their journey to becoming a fundraising expert, starting from the basics of fundraising to a broad understanding of the different means and channels through which income can be raised for arts and cultural organisations. This book is a practical and accessible guide to exploring current fundraising thinking, enabling the reader to develop their own fundraising expertise and to embed knowledge and practice into their own organisations. The fundraising experience from industry pioneers sets this book apart and will inspire readers to achieve their own ambitious goals.
OCLC-licensed vendor bibliographic record.
Keywords: Fund raising -- Management; Cultural industries -- Management; Nonprofit organizations -- Finance; BUSINESS & ECONOMICS / Entrepreneurship